Morphological and physiological species-dependent characteristics of the rodent Grueneberg ganglion - Brechbühl, Julien; Klaey, Magali; Moine, Fabian; Bovay, Esther; Hurni, Nicolas; Nenniger-Tosato, Monique; Broillet, Marie-Christine (Frontiers in Neuroanatomy, 2014)
In the mouse, the Grueneberg ganglion (GG) is an olfactory subsystem implicated both in chemo- and thermo-sensing. It is specifically involved in the recognition of volatile danger cues such as alarm pheromones and structurally-related predator scents. No evidence for these GG sensory functions has been reported yet in other rodent species. In this study, we used a combination of histological and physiological techniques to verify the presence of a GG and investigate its function in the rat, hamster and gerbil comparing with the mouse. By scanning and transmitted electron microscopy, we found isolated or groups of large GG cells of different shapes that in spite of their gross anatomical similarities, display important structural differences between species. We performed a comparative and morphological study focusing on the conserved olfactory features of these cells. We found fine ciliary processes, mostly wrapped in ensheating glial cells, in variable number of clusters deeply invaginated in the neuronal soma. Interestingly, the glial wrapping, the amount of microtubules and their distribution in the ciliary processes were different between rodents. Using immunohistochemistry, we were able to detect the expression of known GG proteins, such as the membrane guanylyl cyclase G and the cyclic nucleotide-gated channel A3. Both the expression and the subcellular localization of these signaling proteins were found to be species-dependent. Calcium imaging experiments on acute tissue slice preparations from rodent GG demonstrated that the chemo- and thermo-evoked neuronal responses were different between species. Thus GG neurons from mice and rats displayed both chemo- and thermo-sensing, while hamsters and gerbils showed profound differences in their sensitivities. We suggest that the integrative comparison between the structural morphologies, the sensory properties and the ethological contexts supports species-dependent GG features prompted by the environmental pressure